Argyria mimicking a blue nevis: dermoscopy features Argyria imitando um nevo azul: características dermatoscópicas - Maria Leonor Enei; Francisco Macedo Paschoal; Rodrigo Valdés (Sociedade Brasileira de Dermatologia, 2013)
Argyria is a rare disease caused by prolonged skin contact with silver. Localized cases have been described regarding the use of topical medications, and trauma with objects containing this metal such as acupuncture needles and jewelry. Clinically, a macule or a patch, round or oval, appears in the infected area, with a characteristic bluey-gray color. To our knowledge this is the first time that this clinical condition has been described through the use of dermoscopy. A argíria é uma doença rara, causada pelo contato prolongado da pele com prata. Foram descritos casos localizados relacionados ao uso de medicamentos tópicos e traumas com objetos que contem esse metal, como agulhas de acupuntura e jóias, por exemplo. Clinicamente, aparecem máculas ou manchas redondas ou ovais na área afetada, com uma característica cor azul-acinzentada. Até onde sabemos esta é a primeira vez que este quadro clínico foi descrito através da dermatoscopia.